Determination of neutral polymorphisms (frameworks) of the human beta globin gene in beta thalassaemias by PCR/DGGE - Moreira, Haroldo Wilson [UNESP]; De Oliveira, Cristina Marta [UNESP]; Martins, Carmen Silvia Bertuzzo; De Sales, Teresa Sueko; Costa, Fernando Ferreira (My University, 1997)
Purpose: Considering the importance of type beta thalassaemias as hereditary syndromes of high significance in different populations of Mediterranean origin and, by extension, in the Brazilian population, the objective of the present study was to determine by PCR/DGGE the gene structures responsible for neutral polymorphisms (frameworks) observed in the human beta globin gene associated with the mutations responsible for type beta thalassaemias in a sample of the Brazilian population and, more specifically, of the population of the State of São Paulo. Patients and methods: Thirty individuals with beta thalassaemic mutations were analyzed: 22 mutations were in codon 39 (C->T), 5 in IVS1-110 (G->A), 2 in IVS1-6 (T->C) and 1 in IVS1-1 (G->A). DNA was extracted and selective amplification was performed by PCR extending from position IVS1 nt 46 to IVS2 nt 126 (474 pb). The product was then analyzed by polyacrylamide gel electrophoresis on a denaturing 10-60% urea/formamide gradient. Results: The results demonstrated that, as expected, the mutations responsible for type beta thalassaemia observed in this population are of Mediterranean origin, with 73% distribution represented by codon 39,17% by IVS1-110, 7% by IVS1-6 and 3% by IVS1-1. In turn, framework distribution seems to indicate a higher frequency of Fr 1-1 in codon 39 and IVS1-110, of Fr 1-3 in IVS1-6 and of Fr 1-2 in IVS1-1. Conclusions: These results permit us to conclude that gene amplification by PCR followed by DGGE is an appropriate method for the separation of DNA molecules that differ even by a single base change and therefore can be utilized to detect the alterations observed in the human beta globin gene. This methodology shows that, using only a pair of primers, it is possible to define the frameworks that are observed in the beta globin gene.
Keywords: dithiothreitol; globin; papain; adolescent; adult; beta thalassemia; Brazil; DNA denaturation; ethnology; female; genetic polymorphism; genetics; human; Italy; male; middle aged; polyacrylamide gel electrophoresis; polymerase chain reaction; Portugal; Spain; Adolescent; Adult; beta-Thalassemia; Dithiothreitol; Electrophoresis, Polyacrylamide Gel; Female; Globins; Humans; Male; Middle Aged; Nucleic Acid Denaturation; Papain; Polymerase Chain Reaction; Polymorphism, Genetic